2016
DOI: 10.1007/s12011-016-0857-2
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Silicate Inositol Complex Accelerates Cutaneous Wound Healing

Abstract: Arginine silicate inositol (ASI) complex is a composition of arginine, silicon, and inositol that has been shown to have beneficial effects on vascular health. This study reports the effects of an ASI ointment on wound healing in rats. A full-thickness excision wound was created by using a disposable 5 mm diameter skin punch biopsy tool. In this placebo-controlled study, the treatment group's wound areas were covered by 4 or 10 % ASI ointments twice a day for 5, 10, or 15 days. The rats were sacrificed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Jung et al, 2015;Lipner, 2018). In a previous study, we conducted to reveal ASI's properties on wound healing, and we found that granulation tissue grew faster in ASI-treated groups than in the control group (Durmus et al, 2017). Besides, Proctor et al (Proctor et al, 2007) demonstrated that ASI is easily and directly absorbed in vivo, as shown by increased plasma arginine concentrations in ASI-treated rats.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Jung et al, 2015;Lipner, 2018). In a previous study, we conducted to reveal ASI's properties on wound healing, and we found that granulation tissue grew faster in ASI-treated groups than in the control group (Durmus et al, 2017). Besides, Proctor et al (Proctor et al, 2007) demonstrated that ASI is easily and directly absorbed in vivo, as shown by increased plasma arginine concentrations in ASI-treated rats.…”
Section: Discussionmentioning
confidence: 89%
“…Photoaging is a skin condition resulting from the chronic and cumulative effects of long-term exposure to UV radiation and is characterized by epidermal thickening, accumulation of abnormal elastin-containing material, deep wrinkles, and abnormal pigmentation (Gragnani et al, 2014). Arginine and biotin exert beneficial effects on vascular function, collagen deposition and synthesis, protein synthesis, and cell proliferation, all of which are crucial for skin health and prevent and control the photoaging process (Dorner et al, 2009;Zempleni et al, 2009;Kalman et al, 2015;Durmus et al, 2017;Mock, 2017). Thus, in the current study, we studied the protective effects of ASI and MgB (a newly produced and highly absorbed biotin salt) orally, with and without MgB topically, on preventing UVB-induced skin photoaging in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Durmus et al observed a significant increase in expression level of the molecules in ASI-treated skin injuries. Durmus et al concluded that topical use of ASI cream (particularly 4% density) has favorable impacts on the curing reaction of an excisional skin injury simulation in rats [8]. Angiogenesis plays an important function in skin injury repair [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, abovementioned potentials have not yet advanced to medical use globally [7]. Very recently, Durmus et al proposed that topical use of a mixture of arginine, silicon, and inositol (ASI) cream has favorable impacts on the curing reaction of an excisional skin injury simulation in rats [8]. Further documents for beneficial effectiveness of arginine in skin injury repair in sick persons originates from a probe by Debats et al who described that arginine supplementation hastens superficial skin injuries in sick persons [9].…”
Section: Introductionmentioning
confidence: 99%